“SOIS VOSOTROS VALIENTES HÉROES. SOMOS NOSOTROS SIMPLES HUMANOS”. LA EXPERIENCIA DE LA GUERRA DEL PACÍFICO EN LOS TESTIMONIOS DE LOS ACTORES - Coronado Canales, David Angelo (2012)
The work we are presenting is a detailed analysis of developments in space as men of the great European developed nodules trade in Southeast Asia. Based on a theoretical analysis, and analyzing 250 maps, we have sequenced the process of perception and geographic market between 1500 and 1800. We have conducted two computations: mapping the weight of all the major ports, and secondly, the relative weight mapping. This lets us know that was what was “perceived” and determine the “pace” of changing the perception of space.